Magnesium-based nanocomposites : advances and applications - Seetharaman, Sankaranarayanan; Tekumalla, Sravya; Gupta, Manoj (IOP ebooks. 2020 collection., 2020)
Magnesium-Based Nanocomposites: Advances and applications covers the most recent advances in the processing and properties of magnesium-based nanocomposites, a class of lightweight sustainable materials with the potential to be revolutionary energy-saving materials with a range of beneficial applications. It provides a complete picture of the materials, including their multi-faceted design and applications in technology, electronics, medicine, and the automotive and aerospace industries. The book will enable researchers and engineers, irrespective of their discipline, to better exploit the benefits of magnesium-based nanocomposites for multiple applications that can contribute significantly to the safe health of humans and the planet. It also acts as a guide for tailoring materials for targeted applications, and as useful supplementary reading for advanced courses on composites and nanocomposites.